Hubungan Konsumsi Suplemen Kalsium yang Kurang Selama Kehamilan sebagai Risiko Kejadian Preeklampsia di Rumah Sakit Umum Daerah (RSUD) Kota Agung Kabupaten Tanggamus - Rendika Oktavia Widiastuti; Dyah Wulan Sumekar; Ratna Dewi PS; Rodiani (Medula, 2020)
Preeclampsia is one form of hypertension in pregnancy. The proportion of hypertension in pregnancy as the leading cause of maternal mortality is increased compared with bleeding and infection. There are potential benefits from the consumption of calcium supplements during pregnancy that decrease preeclampsia. The Purpose of this study was to determine the risk of consuming fewer calcium supplement during pregnancy to the incidence of preeclampsia at RSUD Kota Agung Kabupaten Tanggamus. The design of this study is case-control. The case population was pregnant women with preeclampsia and the control population was pregnant women without preeclampsia. The sample of case consists 46 respondents and sample of control consists 46 respondents. Incidence of preeclampsia data was obtained from the KIA book, while consumption of calcium supplement from the questionnaire. Bivariate analysis using Chi-square. In pregnant women with preeclampsia more who consuming less calcium (65.2%) than the control group (34.8%). Based on bivariate analysis, p = 0.004 and OR 3.875 (95% CI: 1.632 – 9.203). Consumption of fewer calcium supplements during pregnancy may increase the risk of preeclampsia by 3.8 times when compared with those consuming enough calcium supplements during pregnancy.